Expansion of Monocytic Myeloid-Derived Suppressor Cells in Patients Under Hemodialysis Might Lead to Cardiovascular and Cerebrovascular Events - Xing, Yan-Fang; Cai, Jia-Rong; Qin, Jun-Jian; Zhou, Wen-Ying; Li, Can-Ming; Li, Xing (Frontiers in Immunology, 2021)
Background：The specific mechanism of cardiovascular and cerebrovascular vasculopathy in the context of end-stage renal disease has not been elucidated. In the present study, we investigated the clinical impact of myeloid-derived suppressor cells (MDSCs) on hemodialysis patients and their mechanism of action. Methods： MDSCs were tested among patients undergoing hemodialysis and their association with overall survival (OS) and cardiovascular and cerebrovascular events was determined. Results： Hemodialysis patients presented with a significantly higher level of monocytic MDSCs (M-MDSCs) compared to healthy controls. M-MDSC were tested 3 months after first testing among 103 hemodialysis patients, with 1 patient not retested due to early death. The repeated results of M-MDSC levels were consistent with the initial results. Patients with persistent M-MDSCs presented decreased OS, as well as increased stroke and acute heart failure events. As illustrated by multivariate Cox regression, M-MDSC was an independent predictor for OS and stroke events of hemodialysis patients. T cell proliferations were significantly abrogated by the addition of hemodialysis-related M-MDSCs in a dose-dependent manner. Besides, M-MDSCs presented higher levels of CXCR4 and VLA-4 compared to monocytes, which indicated their enhanced capability to be recruited to atherosclerotic lesions. The expression of arginase I and activity of arginase was also significantly raised in hemodialysis-related M-MDSCs. Human coronary arterial endothelial cells (HCAECs) presented increased capability to migration by coculture with M-MDSCs, compared with monocyte group. Arginase inhibitor and L-arginine abrogated the immune suppressive function and induction of HCAECs migration of hemodialysis related M-MDSC. Plasma IFN-γ, TNF-α and IL-6 were elevated in hemodialysis patients compared with healthy control. M-MDSC level was positively related to IL-6 level among hemodialysis patients. The plasma of hemodialysis patients induced M-MDSCs significantly compared with plasma from health donors. Besides, IL-6 neutralizing antibody significantly abrogated the induction. Neutralizing antibody of IFN-γ and TNF-α partially decreased the generation of arginase of the induced M-MDSC. Conclusions: M-MDSCs were elevated in ESRD patients under hemodialysis and they exhibited a strong association with the risk of cardiovascular and cerebrovascular diseases. Hemodialysis related M-MDSC presented enhanced recruitment to atherosclerotic lesions, promoted the migration of endothelial cells through exhaustion of local L-arginine.